Malay Mail, 05 February 2015 (Malay Mail Sdn Bhd, 2015)
In a makeshift kitchen on the site of a house ruined by floods in Kampung Laloh here, Rozita Mat Saad and some of her family members cooked nasi goreng ikan bilis (anchovy fried rice) in a big wok.